Key Enzymes in Fatty Acid Synthesis Pathway for Bioactive Lipids Biosynthesis - Zhuang, Xiao-Yan; Zhang, Yong-Hui; Xiao, An-Feng; Zhang, Ai-Hui; Fang, Bai-Shan (Frontiers in Nutrition, 2022)
Dietary bioactive lipids, one of the three primary nutrients, not only was essential for growth and provide nutrients and energy for life's activities but also can help to guard against disease, such as Alzheimer's and Cardiovascular diseases, which further strengthen the immune system and maintain many of the body's functions. Many microorganisms, yeast, algae, and marine fungi, have been widely developed for dietary bioactive lipids production. These biosynthetic processes were not limited by the climate and ground, which also own superiority of shorter periods and high conversion rate. However, the production process was also exposed to the challenges of low stability, concentration, and productivity, which derived from the limited knowledge about the critical enzyme in the metabolic pathway. Fortunately, the development of enzymatic research methods provides powerful tools to understand the catalytic process, including site-specific mutagenesis, protein dynamic simulation, and metabolic engineering technology. Thus, we review the characteristics of critical desaturase and elongase involved in the fatty acids’ synthesis metabolic pathway, which aims to not only provide extensive data for enzyme rational design and modification but also provide a more profound and comprehensive understanding of the dietary bioactive lipids' synthetic process.